Desenvolvimento forrageiro e florestal em sistemas de integração lavoura-pecuária-floresta - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
The extractive practice of Brazilian agriculture has caused soil degradation in more than half of the areas destined for the activity, given the country's expressiveness in the production of animal and vegetable food worldwide, it is necessary to adopt methods for recovery, conservation and intensification of production. The Crop-Livestock-Forest (iCFL) integration has stood out, as this model allows production in the same area in consortium, succession or rotation, however, the number of components in integration is complex and if poorly implanted it promotes antagonism between the components. Therefore, in order to promote synergism, information is needed, above all, about the tree component, due to the time spent in the system and development in relation to the others. The objective of this work was to evaluate forage and forest development in crop-livestock-forest integration systems. The experiment was developed under a latossolo vermelho dystrophic. In the forage component (Urochloa brizantha cv. Marandu), height, SPAD index (chlorophyll content of plants), tiller density, productivity in green and dry mass, leaf: stem ratio (F:C) and percentages of leaf and stem in the mass produced were evaluated. In the tree component, the height of trees, diameter at breast height (DBH) and tree and per hectare were evaluated, the three forest species used were Corymbia citriodora, Eucalyptus cloeziana and Eycalyptus spp. I-144, in two arrangements (single lines and triple lines), three spacings between trees (1, 2 and 3 meters) and three distances from the tree rows (2.5, 5.0 and 7.5 meters). The design was completely randomized in a 3x2x3x3 factorial scheme, totaling 54 treatments, with two replications. LSD test (p <0.05) was used for trees and Tukey forage (p <0.05).For pasture, it was observed that the plants closest to the row of trees expressed less production of MV and DM of grass, however, presented a higher index of the F: C ratio and an increase in the percentage of leaves. For the forest species, an effect of the implantation model was observed in the development of the three species, Clone I144 had the highest performance, Corymbia citriodora intermediary and Eucalyptus cloeziana the lowest. In the triple and denser arrangement there was greater production by area, however less individual.
Keywords: Agrossilvipastoril; Silvicultura; Sistemas integrados; Urochloa brizantha; Agrossilvopastoral; Silvocultural; Intercrop systems.; Urochloa brizantha; CIENCIAS AGRARIAS